(untitled) (Bangladesh Journal of Psychiatry, 2017)
Major Depressive Disorder (MDD) is a significant public health problem due to its impact on the quality of life. The aim of the study was to determine the presentation of depression in different age group and quality of life among the respondents. This was a descriptive cross sectional study conducted from May, 2012 to February, 2013 among 65 patients aged 18 to 65 years with major depressive disorder in both outpatient and inpatient departments of National Institute of Mental Health (NIMH), Dhaka by using convenient sampling technique. Diagnostic and Statistical Manual of Mental Disorders- Text version (DSM-IV-TR), Beck Depression Inventory and World Health Organization Quality of Life Scale, Brief version (WHOQOL-BREF) were used to diagnose depressive disorder, to measure severity of depressive illness and Quality of Life (QOL) respectively. Level of depression was compared with the QOL. Quality of life deteriorated in patients with depression. Presence and level of depression was compared in different age groups of depressed patients. The results showed that most of the depressed people (17) were found in the age group of 21-25 years and most of the patients were severely depressed which was thirty nine (39). The study revealed that young people were mostly depressed and their quality of life was decreasing. lt needs further study to explore more information about pattern of presentation of depression and its effect on the quality of life. Bang J Psychiatry Dec 2014; 28(2): 58-61